Evaluation of the CSM‐CROPGRO‐Canola Model for Simulating Canola Growth and Yield at West Nipissing in Eastern Canada. (1st March 2016) - Jing, Qi; Shang, Jiali; Qian, Budong; Hoogenboom, Gerrit; Huffman, Ted; Liu, Jiangui; Ma, Bao‐Luo; Geng, Xiaoyuan; Jiao, Xianfeng; Kovacs, John; Walters, Dan
Abstract : With increasing demands for renewable energy and dietary vegetable oils, the production of canola has become widespread in recent years. Modeling canola growth and yield is a helpful approach to predict canola responses to various environments, especially under climate change. However, few studies have been performed for predicting growth and yield of canola in Canada. In this study, we evaluated the CSM‐CROPGRO‐Canola model in Decision Support System for Agrotechnology Transfer v4.6 for simulating spring canola at West Nipissing in Eastern Canada. The model was evaluated using plant and soil data collected from field experiments over three growing seasons (2012–2014). The model could predict the observed crop development and successfully mimic the characteristics of canola regarding light absorption and utilization using combinations of leaves and pods. The accumulations of aboveground biomass were satisfactorily simulated in the life cycle under different nitrogen (N) fertilizer application rates, with a normalized RMSE of 19%. The seed yields were successfully predicted with different N application rates except for an underestimation under zero N application. The underestimation of yield under low N rates was possibly related to the deficiency in the simulated N mineralization that could also be associated with inaccurate input soil data. A better simulation of seed yields under low N application was achieved when the soil organic matter module based on the CENTURY model was used in DSSAT v4.6. The calibrated model simulated soil moisture and inorganic N contents satisfactorily, showing a good performance of the CSM‐CROPGRO‐Canola model for the study region.